Greater Trochanteric Pain Syndrome - Klauser, Andrea S.; Martinoli, Carlo; Tagliafico, Alberto; Bellmann-Weiler, Rosa; Feuchtner, Gudrun M.; Wick, Marius; Jaschke, Werner R. (Seminars in Musculoskeletal Radiology, 2013)
Pain around the greater trochanter is still a common clinical problem that may be secondary to a variety of either intra-articular or periarticular pathologies. Gluteal tendon pathologies are one of the primary causes of greater trochanteric pain, with attrition of the fasciae latae against the gluteus medius and minimus tendons, and the trochanteric bursa being possible causes. Key sonographic findings of gluteal tendinopathy, bursitis, and differential diagnosis are described in this overview. Clinical diagnosis and treatment of greater trochanteric pain syndrome is still challenging; therefore ultrasound is helpful to localize the origin of pain, determine underlying pathology, and, based on these findings, to guide local aspiration and/or injection in cases of tendinopathy and/or bursitis.
Keywords: gluteus; greater trochanter; ultrasound; bursa